Associations between drugs and small‐bowel mucosal bleeding: Multicenter capsule‐endoscopy study. Issue 1 (4th September 2017) - Niikura, Ryota; Yamada, Atsuo; Maki, Koutarou; Nakamura, Masanao; Watabe, Hirotsugu; Fujishiro, Mitsuhiro; Oka, Shiro; Esaki, Motohiro; Fujimori, Shunji; Nakajima, Atsushi; Ohmiya, Naoki; Matsumoto, Takayuki; et al.
Abstract : Background and Aim: Although several drugs may induce small‐bowel mucosal injuries, it is unclear whether these injuries contribute to overt small‐bowel bleeding. This study was designed to evaluate the associations between drug use and small‐bowel mucosal injury and between these mucosal injuries and overt bleeding in a disease‐relevant population. Methods: We retrospectively studied patients with suspected small‐bowel diseases who underwent capsule endoscopy between 2010 and 2013. Drug exposure, Charlson Comorbidity Index, smoking, and alcohol consumption were assessed before capsule endoscopy. Adjusted odds ratios (AOR) and confidence intervals (CI) were estimated for small‐bowel mucosal injury and small‐bowel overt bleeding. Results: In total, 850 patients were analyzed during the study period. Median age was 64 years, and 544 patients (64.0%) were men. Among the patients with small‐bowel mucosal injury ( n  = 60) and without mucosal injury ( n  = 705), use of non‐steroidal anti‐inflammatory drugs (NSAIDs) (AOR 1.8, 95% CI 1.01–3.31) was significantly associated with an increased risk of small‐bowel mucosal injury compared with non‐use. Patients with small‐bowel mucosal injury with overt bleeding ( n  = 85) and without overt bleeding ( n  = 60) were compared, and no significant difference between the groups in the usage rates for NSAIDs, thienopyridine, other antiplatelets, anticoagulants, acetaminophen, tramadol hydrochloride, or steroids was revealed, even after adjusting for confounders. Conclusion: Although the use of NSAIDs was significantly associated with an increased risk of small‐bowel mucosal injury, no significant associations were observed between the use of such drugs and small‐bowel overt bleeding.